Introducing the concept of defect tolerance by fatigue spectral methods based on full-field frequency response function testing and dynamic excitation signature. (December 2022) - Zanarini, Alessandro
Abstract: The complete elimination of flaws in complex parts raises the overall costs, especially under stringent safety or service targets, while advanced knowledge might grade the risk of running defected parts with savings. Introducing the novel concept of defect tolerance, this work proposes to exploit experiment-based full-field measurements from optical techniques, in conjunction with fatigue spectral methods and dynamic excitation signatures, for the definition of a macro-scale defect risk index mapping, retaining the most advanced knowledge available about task-related loading, cumulated damage and inherent structural dynamics of a real object in assembling conditions. The acceptance threshold on the risk index map can discriminate among dangerous permutations of defect locations. Meaningful examples are given on an aluminium thin plate, as a lightweight structure with complex structural dynamics. Highlights: The defect tolerance concept and task-oriented acceptance threshold are introduced. Defected parts' risk grading is based on optical full-field FRF testing & NDT. The defined Risk Index retains the whole experiment-based structural dynamics. Defect risk grading is enhanced thanks to experiment-based fatigue spectral methods. Dynamic excitation signatures have deep impact on the defect tolerance mapping.